Factors Influencing the Acceptance of Collaboration Technology within the Context of Virtual Teamwork Training - Godin, Joy Jones (My University, 2013)
The purpose of this dissertation was to identify the factors that influence electronic collaboration technology acceptance and predicted usage for virtual team collaboration projects in higher education courses. The research combined the unified theory of acceptance and usage of technology (UTAUT) with a virtual team training model.
The dissertation, "Factors Influencing the Acceptance of Collaboration Technology within the Context of Virtual Teamwork Training," by Joy Jones Godin.
Keywords: Teamwork Training; Technology; Communications; UTAUT